Effect of Chickpea (Cicer arietinum L.) Flour Incorporation on Quality, Antioxidant Properties, and Bioactive Compounds of Shortbread Cookies - Katarzyna Felisiak; Sylwia Przybylska; Grzegorz Tokarczyk; Małgorzata Tabaszewska; Jacek Słupski; Joanna Wydurska (Foods, 2024)
High nutritional value and antioxidant properties make chickpea flour a valuable substitute for wheat flour, although its texture-forming abilities are different. The aim of this study was to investigate the possibility of increasing the content of bioactive compounds and antioxidant properties of shortbread cookies by simple partial or complete replacement of wheat flour with chickpea flour without considerable changes in texture, color, sensory properties, or acceptability. Shortbread cookies were made from wheat flour (0% of chickpea flour), wheat flour and chickpea flour (replacement of 25%, 50%, and 75%), and chickpea flour (100%). Generally, the increase in chickpea flour share resulted in an increase in protein, fat, and ash content, as well as antioxidant properties. Polyphenol content, flavonoid content, and antioxidant activities increased three- to sixfold in shortbread cookies containing chickpea flour in comparison to wheat cookies. The level of proteins increased about 50% and the antioxidant properties were three to six times higher than in wheat cookies. Cookies containing up to 75% chickpea flour were assessed as very good or good quality, while only cookies without wheat flour were assessed as sufficient quality. It could be concluded that part of the wheat flour content in shortbread cookies can be replaced by chickpea flour. Application of a 25% proportion of chickpea flour increases physicochemical properties without changes in sensory properties. Sensory quality was up to 75% lower, but antioxidant properties were increased. However, complete replacement of wheat flour in shortbread cookies without changing the recipe resulted in a product of slightly lower sensory quality.